Produksi Polyhydroxybutyrate Menggunakan Mikroba yang Dimodifikasi Secara Genetik: Tinjauan Terhadap Keamanan dan Keberlanjutan - Susanto, Feri (MAIYAH, 2023)
Polyhydroxybutyrate (PHB) is a biocompatible and biodegradable polymer that has the potential to replace fossil-derived polymers. The enzymes involved in PHB biosynthesis are β-ketothiolase (PhaA), acetoacetyl-CoA reductase (PhaB), and PHA synthase (PhaC). PHB has properties similar to conventional plastics but can be decomposed naturally by microorganisms in a suitable environment. The production of PHB using genetically modified microbes has become the focus of research in an effort to produce PHB efficiently and sustainably. Production sustainability refers to the ability of an industry to maintain sustainable production without destroying the environment and limited natural resources. By using genetically modified microbes, PHB production can be significantly increased, making it a more sustainable and environmentally friendly alternative to conventional plastics. Non-biodegradable conventional plastics cause serious environmental problems. Therefore, the production of PHB using genetically modified microbes is becoming a relevant topic in the industry today. Keywords: Polyhydroxybutyrate, microorganisms, modification, genetics